2007
DOI: 10.2319/120905-430r.1
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor–α Levels during Two Different Canine Distalization Techniques

Abstract: Objectives:To compare levels of tumor necrosis factor (TNF)-␣ while applying continuous and heavy interrupted forces. Materials and Methods: A hybrid retractor was used in the first group. In the second group, rapid canine distalization through periodontal distraction was performed. Gingival crevicular fluid samples were collected from the distal sides of the canine teeth before attaching the appliances and at 1 hour, 24 hours, and 1 week after the force was applied. Results: In the hybrid reactor group, conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 31 publications
(62 reference statements)
2
33
1
Order By: Relevance
“…Ren et al showed that the level of IL-6 and TNFα significantly increased at 24 hours, and during the linear phase of OTM, concentration of these cytokines decreased almost to the baseline level (24). Differences between our results and those of previous studies may be attributed to different assessment time points and variability in the magnitude of mechanical loads applied, because different magnitudes of tensile load cause different responses in the PDL (25), also, variability in the level of pro-inflammatory mediators is related to the type of load applied and frequency of load activation. Although the level of mediators increases following application of both continuous and interrupted loads, greater level of inflammation is seen following the application of interrupted load (26).…”
Section: Discussioncontrasting
confidence: 95%
“…Ren et al showed that the level of IL-6 and TNFα significantly increased at 24 hours, and during the linear phase of OTM, concentration of these cytokines decreased almost to the baseline level (24). Differences between our results and those of previous studies may be attributed to different assessment time points and variability in the magnitude of mechanical loads applied, because different magnitudes of tensile load cause different responses in the PDL (25), also, variability in the level of pro-inflammatory mediators is related to the type of load applied and frequency of load activation. Although the level of mediators increases following application of both continuous and interrupted loads, greater level of inflammation is seen following the application of interrupted load (26).…”
Section: Discussioncontrasting
confidence: 95%
“…TNF- α is a cytokine involved in bone resorption by being released from osteoblasts as well as monocytes and macrophages in acute and chronic inflammation [17] and under mechanical loading [11, 18]. In the studies, inflammatory cytokines such as IL-1 β and TNF- α have also been reported to increase in GCF as a result of aseptic inflammation caused by orthodontic treatment [19, 20].…”
Section: Discussionmentioning
confidence: 99%
“…Among these studies, further analysis of the titles, abstracts, and fulltexts revealed that 25 were relevant for the present study. A summary of papers that were excluded is presented in Figure 1 (exhibiting the orthodontic mechanics, GCF sampling methods, and cytokine measurements) [1][2][3][4][5][6][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41].…”
Section: Resultsmentioning
confidence: 99%